Variation in aerobic recovery and vigor of cultivated and wild rice genotypes after anaerobic germination stress in rice (Oryza sativa) - L, MANOJ M; N, SREESHMA; MAINKAR, PAWAN S; SINGH, BALWANT; R MITHRA, AMITHA S V C; SINGH, NAGENDRA K (The Indian Journal of Agricultural Sciences, 2021)
Hypoxia due to flooding during germination is a common abiotic stress for direct sown rice (DSR). There are available protocols for evaluating tolerance to anaerobic germination including seedling survival percentage and coleoptile elongation which is helpful in surviving shallow flooding. Here we studied previously underexplored aerobic recovery after extended anaerobic stress during germination and seedling vigor after recovery. A procedure was developed for screening rice (Oryza sativa L.) genotypes for measuring aerobic recovery and vigor of recovery and demonstrated in a set of 20 cultivars and 30 wild rice accessions. Six wild rice accessions (NKSWR52, NKSWR3, NKSWR57, NKSWR226, NKSWR98 and NKSWR83) and cultivar Pokkali showed the highest recovery percentage and three wild rice accessions (NKSWR 97, NKSWR 57 and NKSWR 226) and cultivar Apo showed the most vigorous recovery (grew >4.5 cm in 7 days). The linear correlation analysis of different seed parameters show that there is a high correlation between percentage of aerobic recovery and vigor of recovery of seedlings and low correlation between anaerobic coleoptile elongation and stored carbohydrates in the seeds. This study also suggested that the mechanism behind recovery of rice seedlings from extended hypoxia during germination is due to ability to stay alive by slowing down metabolism and entering to a dormant state.